Pengaruh Penambahan Plastik PET (Polyethylene Terephthalate) dan POFA (Palm Oil Fuel Ash) pada Campuran LASTON AC-WC terhadap Parameter Marshall - Sheva Alviano Aziz; Achmad Aprilian Arifianto; Asri Nurdiana; Riza Susanti (Civil Infrastructure Engineering and Architectural Design, 2023)
PET (Polyethylene Terephthalate) plastic cannot be separated from everyday life, as is commonly found in bottles. The increasing use of plastic, if not managed and utilized correctly, will cause harm to the environment. On the other hand, Indonesia is rated first as a palm-producing country. Unfortunately, its become a new problem due to the waste generated. POFA (Palm Oil Fuel Ash) is palm oil waste in the form of grayish-black fine granules resulting from burning palm oil at a temperature of 800 – 1000°C. POFA waste management is needed so that it does not only become waste but has added value. In addition, the high demand for asphalt mixtures requires innovations to improve the characteristics of asphalt mixtures, such as utilizing PET and POFA waste as additives in asphalt mixtures. This research aimed to determine the marshall parameters of the AC-WC mixture added with PET and POFA, obtain the KAO value (Optimum Asphalt Content), and look for the cost efficiency of the AC-WC mixture. This study designed 45 samples with details of 15 samples to obtain the KAO value and 30 samples to determine the optimum PET content varying from 1%, 2%, and 3%, along with POFA 50% and 100 %. These samples were tested using the Marshall test referring to SNI 2489-2018. This study found that the percentage of 1% and 2% PET met the requirements of the 2018 General Specification Revision 2 with the optimum percentage of adding 2% PET plastic and 50% POFA substitution.